Incidental small renal tumours: are we performing unnecessary surgery?. Issue 2 (7th February 2023) - Warren, Hannah; Tran, Maxine
Abstract : As medical technology develops, cancer can be detected sooner and potentially be treated more effectively. However, the benefits of early detection are not clear. Here the authors discuss whether early detection of kidney cancer is leading to overtreatment of some patients and how newer diagnostic techniques may help improve patient‐centred management of the disease.